2006
DOI: 10.1021/jp055548c
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Mediated Control of Pore Size and Morphology for Molecularly Ordered Ethylene-Bridged Periodic Mesoporous Organosilica

Abstract: A series of ethylene-containing mesoporous organosilica materials were fabricated via surfactant-mediated assembly of 1,2-bis(triethoxysilyl)ethylene (BTEE) organosilica precursor using alkyltrimethylammonium bromide (CnTAB) surfactants with different alkyl chain length (n=12, 14, 16, 18) as supramolecular templates. The presence of molecularly ordered ethylene groups in the resulting periodic mesoporous organosilica (PMO) materials was confirmed by XRD data along with 29Si and 13C MAS NMR analysis. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
(135 reference statements)
0
22
1
Order By: Relevance
“…[4][5][6] Most of these materials have amorphous pore wall structures, that is, the organic groups are randomly arranged within the framework. In a few selected cases [R = C 6 H 4 , [7][8][9][10] (C 6 H 4 ) 2 , [11,12] CH=CH, [7,13,14] CH=CH À C 6 H 4 À CH= CH, [15,16] and 2,6-naphthylene [17] ), the self-organization of bis-silylated organic precursors has been exploited to prepare PMOs with molecular scale ordering of the organic groups within the pore walls. [18,19] The first report of an ordered mesoporous material possessing a crystal-like periodic pore wall structure came from Inagaki et al, who used 1,4-bis(triethoxysilyl)benzene (BTEB) as the precursor to a phenylene-silica hybrid mesoporous material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Most of these materials have amorphous pore wall structures, that is, the organic groups are randomly arranged within the framework. In a few selected cases [R = C 6 H 4 , [7][8][9][10] (C 6 H 4 ) 2 , [11,12] CH=CH, [7,13,14] CH=CH À C 6 H 4 À CH= CH, [15,16] and 2,6-naphthylene [17] ), the self-organization of bis-silylated organic precursors has been exploited to prepare PMOs with molecular scale ordering of the organic groups within the pore walls. [18,19] The first report of an ordered mesoporous material possessing a crystal-like periodic pore wall structure came from Inagaki et al, who used 1,4-bis(triethoxysilyl)benzene (BTEB) as the precursor to a phenylene-silica hybrid mesoporous material.…”
Section: Introductionmentioning
confidence: 99%
“…Bromination experiments performed for vinylene-and phenylenedivinylene-bridged PMOs showed that up to 35% of the organic groups were accessible for functionalization. [14,16] Crystal-like mesoporous phenylene-silica can be sulfonated in one step (by treatment with fuming sulfuric acid or chlorosulfonic acid) or aminated in two steps (by nitration with HNO 3 -H 2 SO 4 followed by treatment with SnCl 2 -HCl). [7,22,23] The amino-functionalized material was found to be a reusable base catalyst for the Knçevenagel condensation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…80 In an NaOH aqueous solution instead of a dilute ammonia solution in ethanol, Kim et al 81 synthesized ordered ethane-bridged PMO spheres with diameters of 1.5 and 2.5 µm by a microwave heating treatment at different temperatures • C). Depending on the alkyl-chain length of the used templates (C n TAB), Mokaya and coworkers 57 found that the morphologies of the ethylene-bridged PMOs gradually changed from monodisperse spheres to rod or cakelike particles and elongated ropelike particles. They also reported that hierarchical superstructures of ethylene-bridged PMOs could be prepared by simply varying the degree of agitation.…”
Section: Pmo Spheresmentioning
confidence: 99%
“…At present, to obtain diversified functional porous silica materials, three general methods (postgrafting, co-condensation, and PMOs (periodic mesoporous organosilicas)) were developed [6][7][8][9][10][11]. The post-grafting refers to the subsequent modification of the inner surfaces of mesostructured silica phases with organic groups, nevertheless, this may lead to pore blocking.…”
Section: Introductionmentioning
confidence: 99%